Hubungan Tingkat Pengetahuan dan Sikap Ibu tentang Perilaku Hidup Bersih Sehat (PHBS) dengan Tingkat Kebersihan Pengelolaan Sarana Sanitasi di Rumah Shelter Dusun Gempol Jumoyo, Salam, Magelang - Putri Dyah Ayu Pratiwi; Siti Hani Istiqomah; Lilik Hendrarini (Poltekkes Kemenkes Yogyakarta, 2012)
One of the government's efforts in tackling the problems of cold lava flood victims of post Merapieruption was building temporary shelter houses or known as huntara. Similar with the common houses, the sanitation facilities of those shelter houses also need maintainance in order to minimize the potentiality of disease spreading. Therefore, the objective of the study was to determine the relationship between the level of knowledge and attitude among housewives on healthy andclean living behavior (PHBS) with the cleanliness and the management of sanitation facilities of shelter houses located at Gempol Village of Jumoyo, Salam, Magelang. The study was a cross sectional survey which involved 80 sampled housewives. The data which were analysed by using chi square test, showed that there are significant correlations between above study variables (p-values < 0.001). Based on that results, it is advised for the housewives to raise their efforts in maintaining and treating the shelter houses which they are living in and always to put into practice the healthy and clean living behavior for their family’s daily activities.